Chromatographic and Computational Assessment of Potential Biological Activity of N-(Substituted Phenyl)- 2-Chloroacetamides Applying Multivariate Methods - Apostolov, Suzana; Vastag, Gyöngyi; Matijević, Borko; Petrović, Slobodan (Journal of liquid chromatography & related technologies, 2015)
The lipophilicity of the newly synthesized N-(substituted phenyl)-2-chloroacetamides, as the most commonly used molecular descriptor of a potential biological activity was the subject of research. The lipophilicity of the tested derivatives was determined by applying the reversed-phase thin-layer chromatography (RPTLC 18F254s ) in mixtures of water and one protic (n-propanol) and one aprotic (acetonitrile) solvent, as well as mathematically. The effects of the substituent on the lipophilicity of chloroacetamides were discussed. The obtained chromatographic retention constant, , of examined chloroacetamides was correlated with the standard measure of lipophilicity, log P, and with pharmacokinetic predictors such as human effective permeability in jejunum, P eff , plasma protein binding, PPB, and distribution through blood-brain barrier, log BBB, using linear regression analysis and two multivariate methods, cluster analysis and principal component analysis. All the applied methods gave very similar results, and all the procedures also confirmed the fact that determined by RPTLC could be used as a descriptor to estimate the potential biological activity of N-(substituted phenyl)-2-chloroacetamides.